亦舒《玫瑰的故事》里1980年代香港社会转型期的性别图景和其女性主义思想 = The gender landscape and feminist thought in Yishu's The Story of Rose amid Hong Kong's social transition in the 1980s - 李翊菁 Lee, Alison Yi Jing (Nanyang Technological University, 2025)
亦舒的代表作《玫瑰的故事》以1980年代香港社会转型期为背景，通过对女性与男性形象的细腻刻画，展现该时期独特的性别图景。尽管该作品长期在社会上享有热度，并被视为女性主义意识鲜明的小说，但学界对其研究仍然有限且存在不足，未能充分挖掘其深刻的学术价值。现有研究普遍存在片面倾向，主要表现为对女性角色现代性特质的过度强调，以及对男性角色的忽视，而这种片面解读正源于学界对女性主义这一经历复杂演变过程的概念的误解。这种误解导致对小说的研究长期停留在单一视角，使其深刻性及学术价值被忽略，且无人将其置于创作背景中进行系统剖析。本文通过文本细读，并结合雷温·康奈尔的男性气质理论，探讨小说中两性形象的多元性，并揭示亦舒在其中勾勒的1980年代香港社会转型期性别图景。进一步地，本文将小说置于香港殖民地教育体系及全球女性主义运动的历史语境之中，并结合亦舒的个人经历，深入探讨其在两性形象塑造背后所蕴含的女性主义思考与探索。本文旨在揭示《玫瑰的故事》的深刻性及其学术价值——不仅是研究1980年代香港社会转型期独特性别景观的重要文本，同时也是理解亦舒女性主义思想的关键载体。此外，本文通过引介女性主义理论，纠正当前学界对女性主义的误读，以推动更精准的学术理解。 Yishu’s seminal work, The Story of Rose, is set against the backdrop of Hong Kong’s social transition in the 1980s. Through its nuanced portrayal of both female and male characters, the novel presents a distinctive gender landscape of that era. Despite its enduring popularity and recognition as a novel with a strong feminist consciousness, academic research on this work remains limited and inadequate, failing to fully uncover its profound scholarly value. Existing studies are often one-sided, primarily overemphasizing the modern characteristics of female characters while neglecting male figures. This biased interpretation stems from a misunderstanding of feminism as a concept that has undergone complex evolution. Such misconceptions have led to a prolonged fixation on a singular perspective, overshadowing the novel’s depth and academic significance, with little effort made to systematically analyze it within its historical and creative context. Through close textual reading and an application of Raewyn Connell’s theory of masculinity, this paper explores the diversity of gender portrayals in the novel and reveals the gender landscape of 1980s Hong Kong as delineated by Yishu. Furthermore, this study situates the novel within the historical context of Hong Kong’s colonial education system and the global feminist movement, while also considering Yishu’s personal experiences, to provide a deeper analysis of the feminist reflections embedded in her characterization of gender roles. Ultimately, this paper aims to illuminate the depth and academic value of The Story of Rose—not only as a crucial text for understanding the unique gender dynamics of Hong Kong’s social transition in the 1980s but also as a key medium for interpreting Yishu’s feminist thought. Moreover, by incorporating feminist theories, this study seeks to rectify prevailing academic misconceptions about feminism and promote a more precise scholarly understanding.